Does exercise prescription based on estimated heart rate training zones exceed the ventilatory anaerobic threshold in patients with coronary heart disease undergoing usual-care cardiovascular rehabilitation? A United Kingdom perspective. (April 2020) - Pymer, Sean; Nichols, Simon; Prosser, Jonathon; Birkett, Stefan; Carroll, Sean; Ingle, Lee
Background: In the United Kingdom (UK), exercise intensity is prescribed from a fixed percentage range (% heart rate reserve (%HRR)) in cardiac rehabilitation programmes. We aimed to determine the accuracy of this approach by comparing it with an objective, threshold-based approach incorporating the accurate determination of ventilatory anaerobic threshold (VAT). We also aimed to investigate the role of baseline cardiorespiratory fitness status and exercise testing mode dependency (cycle vs . treadmill ergometer) on these relationships. Design and methods: A maximal cardiopulmonary exercise test was conducted on a cycle ergometer or a treadmill before and following usual-care circuit training from two separate cardiac rehabilitation programmes from a single region in the UK. The heart rate corresponding to VAT was compared with current heart rate-based exercise prescription guidelines. Results: We included 112 referred patients (61 years (59–63); body mass index 29 kg·m –2 (29–30); 88% male). There was a significant but relatively weak correlation ( r  = 0.32; p  = 0.001) between measured and predicted %HRR, and values were significantly different from each other ( p  = 0.005). Within this cohort, we found that 55% of patients had their VAT identified outside of the 40–70% predicted HRR exercise training zone. In the majority of participants (45%), the VAT occurred at an exercise intensity <40% HRR. Moreover, 57% of patients with low levels of cardiorespiratory fitness achieved VAT at <40% HRR, whereas 30% of patients with higher fitness achieved their VAT at >70% HRR. VAT was significantly higher on the treadmill than the cycle ergometer ( p <  0.001). Conclusion: In the UK, current guidelines for prescribing exercise intensity are based on a fixed percentage range. Our findings indicate that this approach may be inaccurate in a large proportion of patients undertaking cardiac rehabilitation.